The cracks in Mapuche song: language, territory, and acoustic colonialism in the poetry of Leonel Lienlaf (Revista de Crítica Literaria Latinoamericana, 2014)
In this article, I analyze texts by Mapuche poet Leonel Lienlaf considering poems from his two published books to date: Se ha despertado el ave de mi corazón (1989) y Pewma dungu/Palabras soñadas (2003), both written in Mapudungun and Spanish. I propose to read his written poetry as a ritualization of voices, sounds and images that emerge from a Mapuche view of language and territory. My analysis highlights the way in which Lienlaf’s poetic texts constitute registers of aural and sound experiences that resist what I call the “acoustic colonialism” imposed by the state, corporate and media agents that dominate the scene of neoliberal Chile.
Keywords: Leonel Lienlaf; Mapuche poetry; language; territory; acoustic colonialism